Is it possible to reach the catheter target proposed by the guidelines? Reasons for catheter use in prevalent hemodialysis patients - M. Dolores Arenas; Ramiro Cazar; Alfredo Cordón; Angel Méndez; Mariano Acuña; Karina Furaz; David Hernan; Paula Manso; Fabiola Dapena; Florentina Rosiqué; Laura Martinez; Leonor Andúgar; et al. (Nefrología (English Edition))
Introduction: Despite the recommendations of the clinical guidelines, the percentage of central venous catheters (CVC) continues to be above the recommended standards. We do not know whether the increasing use of catheters is due to unavoidable or avoidable factors and, in the latter case, it would be in our power to modify these results.The aim of this study was to analyze the causes that condition the use of CVC in a prevalent hemodialysis (HD) population in order to identify those modifiable factors on which to act in order to achieve the objectives of the guidelines. Methods: Retrospective, descriptive and observational study in all prevalent patients on chronic hemodialysis belonging to 7 hemodialysis centers in Madrid, Castilla-León and Galicia in a cross-sectional study carried out in June 2021 (637 patients). The following were analyzed: age, sex, nationality, etiology of CKD, the vascular access with which they started hemodialysis, the number of previous failed arteriovenous fistulas (AVF), time since the start of HD, time since the placement of the CVC for the first time, the situation with respect to surgery and the causes of being a CVC carrier. In patients whose cause was refusal to undergo AVF, patients were asked about the cause of the refusal by directed questioning. Results: Of the 637 patients studied, 255 (40%) had a CVC, 346 had an AVF (54.3%) and 36 (5.7%) had a prosthesis. Of the 255 patients with CVC, 20.4% (52 p) were awaiting vascular access (AVF/prosthesis), 10.2% (26 p) had an AVF but could not be used and 69.4% (177 p) were not considered candidates for surgery (due to vascular surgery (16.9%; 43 pac), nephrology (16.5%, 42 pac) and patient refusal (36%; 92 pac). The most frequent cause for refusal of AVF was fear and patient preference. One of the most important factors associated with CVC use in prevalent patients was having started hemodialysis with a CVC. The greatest use of CVC at the start of HD was significantly associated with having more than one AVF performed, or starting HD urgently and not having been followed up and evaluated in the ACKD consultation. Conclusions: There is a high percentage of patients with a central venous catheter due to modifiable causes, which makes it necessary to systematically evaluate the process of creating AVF in order to enhance the planning, creation and maintenance of vascular access from the ACKD clinic, and to achieve the objective of the guidelines. Resumen: Introducción: A pesar de las recomendaciones de las guías clínicas, el porcentaje de catéteres venosos centrales (CVC) sigue estando por encima de los estándares recomendados. Desconocemos si la utilización creciente de catéteres tiene su origen en factores inevitables o evitables y, en este último caso, estaría en nuestra mano modificar estos resultados.El objetivo de este estudio ha sido analizar las causas que condicionan el uso de CVC en una población prevalente en hemodiálisis (HD)con el fin de identificar aquellos factores modificables sobre los que actuar para conseguir los objetivos de las guías. Métodos: Estudio retrospectivo, descriptivo y observacional en el total de pacientes prevalentes en hemodiálisis crónica pertenecientes a 7 centros de hemodiálisis extrahospitalarios de Madrid, Castilla-León y Galicia en un corte transversal realizado en junio 2021 (637 pacientes). Se analizan: edad, sexo, nacionalidad, etiología de la ERC, el acceso vascular con el que iniciaron hemodiálisis, el número de Fístulas arteriovenosas (FAV) previas fallidas, tiempo desde el inicio de la HD, tiempo desde la colocación del CVC por primera vez, la situación respecto a la cirugía y las causas de ser portador de CVC. En los pacientes cuya causa fue la negativa a realizarse una FAV se preguntó a los pacientes por la causa de la misma mediante interrogatorio dirigido. Resultados: De los 637 pacientes estudiados, 255 (40%) eran portadores de CVC, 346 portadores de FAV (54,3%) y 36 (5,7%) llevaban una prótesis. De los 255 pacientes portadores de CVC, el 20,4% ( 52 p) estaba pendiente de realización del acceso vascular (FAV/ prótesis), un 10,2% (26 p) tenían la FAV realizada pero no se podía utilizar y un 69,4% (177 p) no se consideraron candidatos a cirugía (por cirugía vascular (16,9%; 43 pac), por nefrología (16,5%, 42 pac) y por negativa del paciente(36%; 92 pac). La causa más frecuente para la negativa a la FAV fue el miedo y las preferencias de los pacientes. Uno de los factores más importantes asociados al uso de CVC en pacientes prevalentes fue haber iniciado hemodiálisis mediante un CVC. El mayor uso de CVC al inicio de HD se asoció significativamente con tener más de una FAV realizada, o iniciar HD de manera urgente y no haber sido seguido y evaluado en la consulta de ERCA. Conclusiones: Existe un elevado porcentaje de pacientes con catéter venoso central por causas modificables que hace necesaria la evaluación sistemática del proceso de creación de FAV para potenciar la planificación, creación y mantenimiento del acceso vascular desde la consulta de ERCA, y alcanzar el objetivo de las guías.